Informational Efficiency in Futures Markets for Crude Oil - Andreas Fritz; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2012)
This paper develops a methodology to test whether recent developments on world oil markets are in line with the hypothesis of efficient markets. We treat the joint hypothesis problem as stated by Fama (1970), Fama (1991), that market efficiency can only be assessed in conjunction with a price model of market equilibrium. Data on spot and futures prices for Brent crude oil in the period 2002-2008 are used in combination with a multi factor model to investigate whether futures prices are efficient forecasts of future spot prices. The hypothesis of market efficiency is assessed by comparing the observed developments of crude oil spot prices to the ex-ante expected distributions of spot prices using the Rosenblatt transform. For the Brent crude oil futures market, the results are in line with the hypothesis of market efficiency in the short-term but during our sample period the hypothesis is refuted when forecast horizons of one year are considered. Our findings suggest that it can lead to rather wrong investment decisions when relying on longer-term crude oil futures prices and the information contained therein.
Keywords: G13; G14; Q40; 330; Multi factor model; Informational efficiency; Oil market